PENGARUH GREEN MARKETING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE BODY SHOP INDONESIA (Studi Kasus Pada Followers Account Twitter @TheBodyShopIndo) - Setiawan, Cruisietta Kaylana; Yosepha, Sri Yanthy (JURNAL ILMIAH M-PROGRESS, 2020)
This research aims to determine the influence of Green Marketing and Brand Image to purchasedecisions of The Body Shop Indonesia product empirically, both partially and simultaneously. Thepopulation of this research is a Twitter account follower @The Body Shop Indo who has made a productpurchase at least twice in the last year. The study used samples of 100 respondents in which a questionnairewas implemented through direct message facilities on Twitter social media. Sampling uses non-probabilitysampling method with purposive sampling method. Methods of data analysis using multiple linear regressiontests, with partial and simultaneous hypotheses test processed using SPSS program version 21.0. The results of this research show that the two independent variables, namely green marketing and brandimage, are positive and significant both partially and simultaneously on dependent variables of the purchasedecision. In addition, in this study green marketing and brand Image explained the purchasing decision of52.9%, the rest is 47,1% influenced by other factors. Therefore, further researchers are advised to addanother variable that affects purchasing decision.Keywords: Green Marketing, Brand Image, Purchasing Decision, The Body Shop